Courses
Courses for Kids
Free study material
Free LIVE classes
More
LIVE
Join Vedantu’s FREE Mastercalss

If one of the root of \[{\text{ }}2{x^2} - cx + 3 = 0{\text{ }}\]is 3 and the another equation \[2{x^2} - cx + d = 0\]has equal roots where c and d are real numbers, then d is equal to
\[
  {\text{a}}{\text{. 3}} \\
  {\text{b}}{\text{. }}\dfrac{{{\text{ 49}}}}{8} \\
  {\text{c}}{\text{. }}\dfrac{8}{{49}} \\
  {\text{d}}{\text{. }} - 3 \\
\]

Answer
VerifiedVerified
367.2k+ views
Hint- In quadratic equation the sum of the roots is${\text{ = }}\left( {\dfrac{{ - {\text{coefficient of }}x}}{{{\text{coefficient of }}{x^2}}}} \right)$, and the product of the roots ${\text{ = }}\left( {\dfrac{{{\text{constant term}}}}{{{\text{coefficient of }}{x^2}}}} \right)$

As we know in quadratic equation the sum of the roots is ${\text{ = }}\left( {\dfrac{{ - {\text{coefficient of }}x}}{{{\text{coefficient of }}{x^2}}}} \right)$
So, first equation is \[{\text{ }}2{x^2} - cx + 3 = 0{\text{ }}\]
Let the roots of this equation be $\alpha ,{\text{ }}\beta $
It is given that one of the root is 3
So, let $\alpha {\text{ = 3}}$
$ \Rightarrow $Sum of the roots${\text{ = }}\alpha {\text{ + }}\beta {\text{ = }}\left( {\dfrac{{ - {\text{coefficient of }}x}}{{{\text{coefficient of }}{x^2}}}} \right) = \dfrac{c}{2}$
$ \Rightarrow 3 + \beta = \dfrac{c}{2} \Rightarrow \beta = \dfrac{c}{2} - 3................\left( 1 \right)$
And the product of the roots $\alpha \beta {\text{ = }}\left( {\dfrac{{{\text{constant term}}}}{{{\text{coefficient of }}{x^2}}}} \right) = \dfrac{3}{2}$
$ \Rightarrow 3\beta = \dfrac{3}{2} \Rightarrow \beta = \dfrac{1}{2}$
So, from equation 1
$
  \beta = \dfrac{c}{2} - 3 \Rightarrow \dfrac{1}{2} = \dfrac{c}{2} - 3 \Rightarrow \dfrac{c}{2} = \dfrac{7}{2} \\
   \Rightarrow c = 7................\left( 2 \right) \\
$
Another given equation is \[2{x^2} - cx + d = 0\]
It is given its roots are equal
So let its roots are $\lambda ,\lambda $
$ \Rightarrow $Sum of the roots${\text{ = }}\lambda {\text{ + }}\lambda {\text{ = }}\left( {\dfrac{{ - {\text{coefficient of }}x}}{{{\text{coefficient of }}{x^2}}}} \right) = \dfrac{c}{2}$
$ \Rightarrow 2\lambda = \dfrac{c}{2}$
From equation (2)
$ \Rightarrow 2\lambda = \dfrac{7}{2} \Rightarrow \lambda = \dfrac{7}{4}$
And the product of the roots $\lambda \lambda {\text{ = }}\left( {\dfrac{{{\text{constant term}}}}{{{\text{coefficient of }}{x^2}}}} \right) = \dfrac{d}{2}$
$
   \Rightarrow {\lambda ^2} = \dfrac{d}{2} \Rightarrow {\left( {\dfrac{7}{4}} \right)^2} = \dfrac{d}{2} \\
   \Rightarrow \dfrac{d}{2} = \dfrac{{49}}{{16}} \Rightarrow d = \dfrac{{49}}{8} \\
$
So, option (b) is correct.

Note- In such types of questions the key concept we have to remember is that always remember the sum and product of roots of the quadratic equation which is stated above, then apply these formulas in the given equations and after simplification we will get the required answer.
Last updated date: 01st Oct 2023
Total views: 367.2k
Views today: 8.67k